2020
DOI: 10.1002/crt2.27
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain fatty acids in sarcopenia patients with cardiovascular diseases: importance of n‐9 monounsaturated fatty acids

Abstract: BackgroundLong‐chain fatty acids are essential components of the cellular energy supply, cellular membranes, and autacoid synthesis. It has been suggested that long‐chain fatty acids might be involved in the pathophysiology underlying sarcopenia. We investigated the association between sarcopenia and serum long‐chain fatty acid profile in patients with cardiovascular diseases.MethodsWe retrospectively investigated 308 cardiovascular patients [age: 72 ± 12 (mean ± SD), 174 male patients] admitted to our hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 34 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Numerous clinical studies have reported that a higher proportion of monounsaturated fats in the diet reduces the risk of cardiovascular diseases through decreasing low‐density lipoprotein cholesterol (LDL‐C) levels in the blood. [ 6 ] In addition, Table 1 show that the table olives contain a considerable amount of polyunsaturated fatty acids (PUFA) as linoleic (C18:2) and linolenic acid (C18:3). The percentage of PUFA was significantly different among the three Tunisian cultivars ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous clinical studies have reported that a higher proportion of monounsaturated fats in the diet reduces the risk of cardiovascular diseases through decreasing low‐density lipoprotein cholesterol (LDL‐C) levels in the blood. [ 6 ] In addition, Table 1 show that the table olives contain a considerable amount of polyunsaturated fatty acids (PUFA) as linoleic (C18:2) and linolenic acid (C18:3). The percentage of PUFA was significantly different among the three Tunisian cultivars ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, clinical studies proved that a higher proportion of monounsaturated fats in the diet reduces the risk of cardiovascular diseases by decreasing low‐density lipoprotein cholesterol (LDL‐C) levels in the blood. [ 6 ] Essential fatty acids, linoleic (C18:2) and linolenic acid (C18:3), are the precursors of the biosynthesis of longer chain PUFA, eicosapentaenoic (C20:5), and docosahexaenoic (C22:6) acids, which are the main constituents of the neural cell membrane. [ 7 ] In addition to the glyceridic components, vegetable matrices regroup several unsaponifiable compounds such as sterols, triterpenic alcohols and policosanol, which display important biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The studies were published between 2006 and 2021. The countries in which the studies were conducted were Spain [ 29 , 31 ], Brazil [ 32 , 33 ], Japan [ 36 , 38 ], Canada [ 30 ], Iran [ 34 ], Finland [ 35 ], the Netherlands [ 39 ], and UK [ 40 ], and one study was conducted in multiple European countries [ 37 ]. All studies included both men and women, except for one study that included only men [ 35 ] and one that included only women [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic criteria for sarcopenia were the EWGSOP [ 31 ], the EWGSOP2 [ 33 35 , 37 , 39 ], the AWGS [ 36 , 38 ], and other diagnostic criteria [ 29 , 30 , 32 , 40 ]. Seven of the included studies diagnosed confirmed/severe sarcopenia [ 31 , 33 , 35 , 36 , 38 40 ], and two studies determined probable sarcopenia among the participants [ 34 , 35 ]. Additionally, Abete 2019 calculated sarcopenic index [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation